Issues in contemporary critical theory : a casebook (Macmillan, 1987)
Examines the issues which have provoked the current 'crisis' in literary studies--including the notion of the 'death of the author', the reader's role in 'creating' the text, the nature of literary representation itself, and the challenge offered to conventional approaches by stylistics and deconstruction. Debate on these issues has transformed literary criticism since the 1960s.